Penerapan Ai Dan Iot Berbasis Arduino Dalam Edukasi Elektronika Di Ma Al-Khairiyah Pekalongan Kelurahan Deringo Kota Cilegon: Pengabdian - Tb Ade Rahmatullah; R Dewi Mutia Farida; Aris Himawan; Firdaus Salam; Muhammad Dandi; Salsanabila Mariestiara Putri (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The development of Artificial Intelligence (AI) and the Internet of Things (IoT) has significantly impacted the field of electronics. This community service program aims to provide fundamental knowledge of AI and IoT concepts and introduce their practical implementation through Arduino-based microcontroller projects. The program consisted of socialization, training, and demonstration of systems applicable in monitoring and simple automation. The results showed an increase in participants' understanding of AIoT concepts and their ability to operate IoT-based devices. Participants were also able to design simple prototypes by integrating sensors and actuators. This activity is expected to provide academic communities and electronics practitioners with essential knowledge and initial skills to face AIoT technological developments.